PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP MINAT MENABUNG NASABAH PADA PT BANK MAYAPADA INTERNASIONAL TBK CABANG DANAU SUNTER - Listra Nataly; Allan Yuda Patria Lai Wie (STIE Wiyatamandala, 2022)
This research was conducted to determine the effect of Product Quality, Service Quality, and Trust either partially or simultaneously to Saving Intention at PT Bank Mayapada Internasional Tbk Branch Danau Sunter. In this study, we used a purposive sampling technique with 76 respondents. The research instrument used a questionnaire that was processed with the IBM SPSS Statistics application, followed by data analysis using multiple linear regression. The results showed that the variables of Product Quality (X₁), Service Quality (X₂), and Trust (X₃) simultaneously had a positive and significant effect on Saving Intention (Y). Partially, only Product Quality (X₁) has a significant effect on Saving Intention (Y). Service Quality (X₂) and Trust (X₃) variables have no significant effect on Saving Intention (Y). The results of the coefficient of determination test (R²) show a result of 0.488, or 48.8%, which means that the three independent variables have an influence of 48.8% on Saving Intention (Y). Meanwhile, 51.2% is influenced by other variables not examined in this research.